METHOD OF PRODUCING CYCLOHEXASILANE COMPOUNDS - ELANGOVAN ARUMUGASAMY; BOUDJOUK PHILIP R; ANDERSON KENNETH; SCHULZ DOUGLAS L (2012)
A method of preparing a cyclohexasilane compound from trichlorosilane is provided. The method includes contacting trichlorosilane with a reagent composition to produce a compound containing a tetradecahalocyclohexasilane dianion, such as a tetradecachlorocyclohexasilane dianion. The reagent composition typically includes (a) tertiary polyamine ligand; and (b) a deprotonating reagent, such as a tertiary amine having a pKa of at least about 10.5. Methods of converting the tetradecahalocyclohexasilane dianion-containing compound to cyclohexasilane or a dodecaorganocyclohexasilane are also provided.